Single-Center 8-Years Clinical Follow-Up of Cladribine-Treated Patients From Phase 2 and 3 Trials - Moccia, Marcello; Lanzillo, Roberta; Petruzzo, Martina; Nozzolillo, Agostino; De Angelis, Marcello; Carotenuto, Antonio; Palladino, Raffaele; Brescia Morra, Vincenzo (Frontiers in Neurology, 2020)
Background. Cladribine is approved for the treatment of highly-active relapsing multiple sclerosis (MS), where it is also effective on disability progression. In the present single-center study, we aim to report on the 8-year clinical follow-up of 27 patients included in phase 2 and 3 clinical trials for cladribine. Methods. We included patients exposed to cladribine (n=13) or placebo (n=14) in ONWARD, CLARITY, and ORACLE-MS trials, and followed-up at the same center after trial termination. Outcomes of long-term disease progression were recorded. Results. During 8-year follow-up, patients treated with cladribine presented with reduced risk of EDSS progression (HR=0.148; 95%CI=0.031, 0.709; p=0.017), of reaching EDSS 6.0 (HR=0.115; 95%CI=0.015, 0.872; p=0.036), and of SP conversion (HR=0.010; 95%CI=0.001, 0.329; p=0.010), when compared with placebo. Conclusions. Our exploratory study provides additional evidence that cladribine may be useful to prevent or, at least, mitigate the risk of disability progression after 8 years.